Ontological and scientific-theoretical challenges of contemporary technology.: A critical perspective - Rynkiewicz, Kazimierz (Studia Teologiczne Białystok Drohiczyn Łomża, 2023)
The esay deals with the problem of contemporary technology in retrospect to consciousness and existence. The question of the nature of technology is examined from a semantic and phenomenological perspective. An ontological balance between being and artifical intelligence is relevant. The hermeneutical handling of technology presupposes a theoretical framework with ethical implications. The nature of technology ultimately remains metaphysically closed, like the nature of time.